The influence of dexmedetomidine added to ropivacaine for transversus abdominis plane block on perioperative neurocognitive disorders after radical colorectal cancer surgery: randomized, double-blind, controlled trial - Li Yang; RongFei Xiong; XingQu Chen; Shu Wang; DeShui Yu (BMC Anesthesiology, 2024)
Abstract Objective Perioperative Neurocognitive Disorders (PND) is a common neurological complication after radical colorectal cancer surgery, which increases adverse outcomes. So, our objective is to explore the influence of dexmedetomidine added to ropivacaine for transversus abdominis plane block (TAPB) on perioperative neurocognitive disorders, and to provide a new way to reduce the incidence of PND. Methods One hundred and eighty patients submitted to radical laparoscopic colorectal cancer surgery were randomly divided into Control group and Dex group. Ultrasound guided TAPB was performed after anesthesia induction: 0.5% ropivacaine 20 ml was injected into each transversus abdominis plane in Control group, 0.5% ropivacaine + 1 μg/kg dexmedetomidine (amounting to 20 ml) in Dex group. We observed the incidence of PND within 30 days after surgery. Results One hundred and sixty-nine cases were finally analyzed, including 84 cases in Control group and 85 cases in Dex group. Compared with Control group, there was no significant difference in terms of the incidence of PND on the 3rd day and the 7th day (P > 0.05), but the incidence significantly decreased at the 6th hour, at the 24th hour and on the 30th day after surgery (P < 0.05) in Dex group. Conclusion Dexmedetomidine added to ropivacaine for TAPB can reduce the incidence of PND in the first 24 h after surgery and on the 30th postoperative day, which may be related to reduce the consumption of general anesthetics and provide satisfactory postoperative analgesia. Trial registration 29 /05/ 2021, ChiCTR2100046876.